Promoting material circularity in pulp and paper mills: organic-inorganic cellulosic composites for slow-release of nutrients - Carzola, Gabriela (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.